Managing Occupational Health And Safety In A Ghanaian Building Industry (A Case Study Of Some Construction Sites Of Eris Property Group In Accra) - Hervie, Dolores Mensah; Oduro-Nyarko, Cynthia (Advances in Social Sciences Research Journal, 2018)
Achieving occupational health and minimisation to a large extent possible hazard to health and safety in the construction industry is the responsibility of all employees. The onus is on management to achieve high standards in such matters as required by the constitution of Ghana (1992) and the Labour Act 2003 (Act 651) in relation to health and safety at the work place. It is high time construction practitioners pay much attention to health and safety issues on sites and implement policies or framework in this regard. The main objective of this study is to find out if contractors and developers in the building industry have health and safety policies and whether these policies are implemented and functional. Through questionnaires, interviews and literature, it was revealed that majority sites have employees’ orientation on health and safety before starting work. More so, management and employees have regular interactions to continuously re-orient the mind on importance of site safety. It also came to light that local contractors are guiltier when it comes to site health and safety practices. Based on the findings from this research, it was recommended that a regulatory body should be formed for the building industry. This body should develop an institutional health and safety framework in line with the constitution and the Labour Act of Ghana that would be stringently implemented in Ghanaian construction sites. Furthermore, international construction sites normally have dedicated department which are well resourced to ensure health and safety measures which local contractors could emulate.